Keanekaragaman Kultivar Mangga (Mangifera indica L.) Di Kabupaten Tangerang - Amalia, Maura Savika; Herawati, Wiwik; Yani, Edy (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
Mango (Mangifera indica L.) is a tropical fruit that is in demand by many people so that it can be found throughout Indonesia. Mangoes have a wide variety of morphology. This diversity occurs because of crossbreeding, natural selection, human influence, evolution and even environmental influences of each location. The research aims to determine the morphological variation of mango cultivars in Tangerang Regency and to know the relationship of similarities based on morphological characteristics. The research was conducted in Tangerang Regency by survey method, with purposive sampling techniques. The bound variables in this study were types of mango cultivars, while free variables covered the height of the place, temperature, humidity, light and pH of the soil. The observed parameters include the morphological characteristics of stems, leaves, fruits and seeds. Mango sample data is analyzed by descriptive method. Medium to know the relationship of similarities analyzed with MEGA X using UPGMA method. The results of research from four sub-districts in Tangerang district found 14 types of cultivars. The similarity relationship based on 22 morphological characteristics results in phenograms divided into 2 main groups. M. indica 'Madu' with M. indica 'Manalagi' and M. indica 'Khiosaway' with M. indica 'Namdokmai' has the closest relationship with the disimilarity index of 0.182. M. indica L. 'Chokanan' and M. indica L. 'Gedong' have the furthest relationship with the disimilarity index of 0.682.